KURIKULUM 2013 SEBAGAI PERWUJUDAN DINAMIKA KONSTRUKTIF YANG BERKARAKTER - Abidinsyah Abidinsyah (Florea : Jurnal Biologi dan Pembelajarannya, 2016)
Constructive dynamics of the curriculum in 2013 became part integrated with changes and developments in the national education curriculum. Through the structure and the basic framework of a scientific approach to a more humane, is expected to print competent future generations to meet the challenges of a more competitive future. Outputs being targeted is the inability of students to thinklogically, systematically, and creative, as well as the character in order to counteract the aberrant behavior. The improvement of the curriculum implementation shortfall in 2013 is expected to bring direction and national education goals more clear and focused.